Posing Arithmetic Problems for Junior High School Students with Different Cognitive Styles - Aminatul Lailiyah; Agung Lukito; Siti Khabibah (Pi: Mathematics Education Journal, 2023)
This study aims to describe the process of posing arithmetic problems for junior high school students with different cognitive styles. The posed problems were assessed based on four processes of posing problems: editing, selecting, comprehending, and translating. Free-type problem posing was used in this study. This study is descriptive research with a qualitative approach. Subject selection was conducted by providing TKM, GEFT, and BSRI. Data collection was conducted through written task and task-based interviews. The subject was two junior high school students. One has Field Dependent (FD) cognitive style, and the other is Field Independent (FI), measured by GEFT. Furthermore, the data were analyzed based on the four processes of posing problems. The results showed that posing arithmetic problems for FI students fulfilled all four processes of posing problems, and posing arithmetic problems for FD students fulfilled three processes for posing problems. In general, the problems raised by the two subjects were problems the subject had encountered or experienced. FD students can pose more problems than FI students.